¿Cómo medir la pobreza? (2010)
ABSTRACT: The Multidimensional Index of Poverty or MPI by its abbreviations in English, is a new measurement of the poverty that gives "a multidimensional" panorama of the people who live in the poverty. The MPI considers a series from essential factors or "deprivations" from the families, from the results in the matter of education and health to the goods and services. The objective is the measurement identifies to the families and the most vulnerable groups and allows to include/understand exactly what deprivations affect their lives.